Information technology: changing nursing processes at the point-of-care. - Courtney KL; Demiris G; Alexander GL (Nursing Administration Quarterly)
Changing societal demographics, increasing complexity in healthcare knowledge, and increasing nursing shortages have led healthcare strategists to call for a redesign of the healthcare system. Embedded within most redesign recommendations is the increased use of technology to make nursing practice more efficient. However, information technology (IT) has the potential to go beyond simple efficiency increases. If IT is perceived truly as a part of the redesign of healthcare delivery rather than simply the automation of existing processes, then it can change nursing processes within institutions and furthermore change the point-of-care between nurses and patients. Nursing adoption of technology within the workplace is a result of the interactions between technical skills, social acceptance, and workplace culture. Nursing needs for information not only influence their adoption of particular technologies but also shape their design. The objective of this article is to illustrate how IT can change not only nursing practice and processes but also the point-of-care. A case study of the use of IT by nurses in telehomecare is presented and administrative implications are discussed.